Tenzor Methods in Cyber Security - Григор’єва Тетяна Ігорівна; Hryhorieva, Tetiana I.; Grygoryeva Tetyana; Йона Лариса Григорівна; Йона, Л. Г.; Yona Larysa; Mazur Anna; Мазур Ганна Дмитрівна (Springer Nature Switzerland AG, 2023)
The development of information technology and intensive use of the Internet has revealed problems related to information security. The issues of protecting information transmitted through communication channels and requiring long-term storage become relevant; the need for authentication procedures for users and messages; improving system performance and reliability. Various tasks ofmodern information security are solvedwith the help of cryptographic protocols. Various sections of higher mathematics are successfully used in information protection tasks. In this article to increase the effectiveness of information protection means, it is proposed to use such a mathematical apparatus as tensor analysis. The possibility of using tensor methods in solving various problems of cryptographic protection of information is shown. As a result of tensor analysis operations, this article shows the possibility of encrypting messages and decrypting cryptograms. The possibility of using tensor analysis in the construction of hash functions is shown additionally. In order to increase the effectiveness of means of protecting conﬁdential information, it is proposed to encrypt messages using tensor analysis operations. At the same time, there is an increase in the speed of the process of ensuring the protection of conﬁdential information in the implementation of document ﬂow.
Hryhorieva T. Tenzor Methods in Cyber Security / T. Hryhorieva T., L. Yona, A. Mazur // Information and Communication Technologies and Sustainable Development. Advanced Approaches and Innovations in Up-to-Date Networks and Systems. Lecture Notes in Networks and Systems. - Springer Nature Switzerland AG. - LNNS 809, 2023. - P. 291–299. https://doi.org/10.1007/978-3-031-46880-3_18
Keywords: Cyber Security; Cryptographic Protection; Encryption Key; Tensor Methods; Hash Function